Nanocomposites with Three-Dimensional Architecture and Impact on Photovoltaic Effect - Mühlenbein L.; Singh C.B.; Lotnyk A.; Himcinschi C.; Yun Y.; Ramakrishnegowda N.; Knoche D.S.; Li X.; Bhatnagar A. (My University, 2025)
We demonstrate the synthesis of self-assembled three-dimensional nanocomposite thin films consisting of NiO nanocolumns in an layered Aurivillius phase matrix. The structures were grown on single-crystal SrTiO3 substrates via pulsed laser deposition (PLD) with single ceramic (PbTiO3)x(BiNi2/3Nb1/3O3)1-x targets. The nanocolumns, which are about 10 nm in diameter each, extend over the entire film thickness of up to 225 nm. We reveal the difference in electrical conduction properties of the nanocolumns and the surrounding matrix on the nanoscale via conductive atomic force microscopy. The nanocomposite thin films exhibit improved photovoltaic performance compared to both pure PbTiO3 and homogeneous Aurivillius phase thin films. © 2020 American Chemical Society.